Metformin and its Effects on Myocardial Dimension and Left ventricular hypertrophy in Normotensive patients with Coronary Heart Disease (The MET‐REMODEL Study): Rationale and Design of the MET‐REMODEL Study. Issue 1 (February 2015) - Mohan, Mohapradeep; McSwiggan, Stephen; Baig, Fatima; Rutherford, Lynn; Lang, Chim C.
Summary Left ventricular hypertrophy (LVH) is a common and independent risk factor for cardiovascular events in patients with coronary artery disease (CAD). Controlling blood pressure is the standard approach to the management of LVH, but this is only partially effective as LVH also persists in normotensive patients. Apart from blood pressure (BP), other main risk factors associated with LVH are insulin resistance (IR) and central obesity. The diabetic medication, Metformin, reduces IR and aids weight loss and may therefore regress LVH. The MET REMODEL study will investigate the ability of Metformin to regress LVH in 64 patients with CAD. The MET‐REMODEL trial is a single‐center, phase IV, double blind, randomized, placebo‐controlled trial to investigate the efficacy of Metformin in regression of the independent cardiac risk factor of LVH in patients with CAD who are insulin resistant. A minimum of 64 adults with a history of CAD with LVH and IR will be randomized into two groups to receive, either Metformin XL or placebo. The primary endpoint of this trial is to investigate any change in left ventricular mass index. Secondary endpoints include changes to insulin resistance measured using fasting insulin resistance index (FIRI), obesity, LV size, and function and improvement in endothelial function. A positive result will assist clinicians to identify a new mechanism for LVH regression by administering Metformin XL. This may also lead to investigating the mortality benefit of Metformin in patients with CAD and LVH.